Granular hydrogel with high mechanical property as well as preparation method and application of granular hydrogel
By mixing specific nanoparticles and polysaccharides under alkaline conditions and adjusting pH with gluconate-δ-lactone, a particle hydrogel with high mechanical properties was prepared, which solved the problem of stability and injectability of existing particle hydrogels in blood vessels, and achieved the effect of forming stable embolism in blood vessels and combining magnetothermal therapy.
Patent Information
- Application Number
- CN202411964791.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing granular hydrogels are easily damaged under the shear and impact of high-speed blood flow, making it difficult to form stable and lasting embolism in arterial blood vessels, and chemical crosslinking methods will affect their injectability and biosafety.
By mixing gelatin nanoparticles, iron oxide nanoparticles, calcium carbonate nanoparticles and sodium alginate under alkaline conditions, and adjusting the pH by using the hydrolysis of gluconate-δ-lactone, a granular hydrogel with high mechanical properties is formed. This method does not involve complex chemical crosslinking, and the raw materials used have good biocompatibility.
It has achieved the significant improvement of the mechanical properties of the particulate hydrogel without affecting the injection properties, so that it can form stable and lasting embolism in the blood vessels, and combined with the magnetothermal effect of magnetic nanoparticles, enhancing the therapeutic effect on tumors.
Smart Images

Figure CN119775597A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, and in particular to a high-mechanical-performance granular hydrogel, a preparation method and application thereof. Background Art
[0002] Primary hepatocellular carcinoma (HCC) is the most common malignant tumor of the liver, accounting for 85% to 90% of all liver cancer cases. There are approximately 700,000 to 800,000 new cases worldwide each year. Transcatheter arterial embolization (TAE) is a mainstream treatment option that can significantly prolong the survival of patients with advanced HCC by selectively injecting embolic agents into the tumor-feeding arteries to block the tumor blood supply and inhibit tumor progression. Traditional embolic agents can be divided into solid embolic agents (polyvinyl alcohol microspheres and gelatin sponge particles) and liquid embolic agents (iodized oil). However, solid embolic agents are limited by their size and cannot fill small and irregular blood vessels. At the same time, they are prone to aggregation and block catheters. In contrast, liquid embolic agents are more suitable for irregular targeted blood vessels. Iodized oil has excellent flow characteristics, can quickly enter the peripheral arteries of tumors, and has good vascular conformity. However, its relatively low mechanical strength is easily cleared by blood flow, resulting in potential vascular recanalization in tumor tissue. Therefore, enhancing the delivery characteristics of embolic agents in blood vessels and improving the mechanical properties of embolic agents are the key to solving the above problems.
[0003] In recent years, shear-thinning hydrogels have attracted great attention in the field of vascular embolic agents because they exhibit fluid-like behavior in the catheter during injection and return to the original gel state after stress is removed. Granular hydrogels, as a type of shear-thinning hydrogel, use nanoparticles as assembly primitives and assemble from bottom to top through non-covalent bonds to form a three-dimensional network structure. When the granular hydrogel network is subjected to external stress or shear, the viscosity decreases sharply and exhibits flow characteristics; once the external force is removed, it can quickly restore its original viscosity and exhibit structural self-repair ability. Granular hydrogels are regarded as highly promising new vascular embolic materials due to their unique rheological properties, excellent biosafety, injectability and catheter deliverability. However, this granular gel network formed by physical non-covalent bonding has weak mechanical properties and is difficult to withstand large external loads, resulting in the granular hydrogel structure being easily destroyed under the shear and impact of high-speed blood flow after implantation in the artery, making it difficult to form a stable and lasting embolism on the artery. Although chemical cross-linking can effectively improve the mechanical properties of particle hydrogels and enhance their structural stability, this technical approach often has a negative impact on the injectability of particle hydrogels, resulting in the inability to be delivered to the tiny blood vessels of the tumor through a catheter, making it difficult to meet the needs of clinical embolization surgery. In addition, chemical cross-linking agents have potential biological toxicity, which limits their application in clinical surgery. Therefore, the development of colloidal gel liver cancer vascular embolic agents with excellent mechanical strength, injectability, deliverability and biosafety still faces difficulties and challenges.
[0004] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of how to improve the mechanical properties of a particle hydrogel without affecting its injectability, and to provide a particle hydrogel with high mechanical properties, a preparation method and an application thereof.
[0006] In order to achieve the above object, the present invention discloses a method for preparing a particle hydrogel with high mechanical properties, comprising the following steps:
[0007] S1, mixing gelatin nanoparticles, iron oxide nanoparticles, calcium carbonate nanoparticles, and sodium alginate under alkaline conditions;
[0008] S2, adding glucono-δ-lactone powder to adjust the pH to obtain a particle hydrogel with high mechanical properties.
[0009] The hydrolysis of glucono-δ-lactone causes the pH to slowly decrease, and the gelatin nanoparticles change from negative charge to positive charge, while the iron oxide nanoparticles still maintain negative charge, and an electrostatic effect is generated between the two particles. Then, the calcium carbonate nanoparticles are acidified by the hydrogen ions produced by the hydrolysis of glucono-δ-lactone, releasing calcium ions, which cross-link with sodium alginate, further enhancing the mechanical properties of the particle hydrogel formed by the above electrostatic effect. In this way, a particle hydrogel with high mechanical properties can be obtained.
[0010] In step S1, the method for preparing gelatin nanoparticles comprises the following steps:
[0011] S111, heating gelatin to dissolve in deionized water to obtain a gelatin solution, adding acetone, standing at room temperature for 1 hour, removing the supernatant, dissolving the precipitate again in deionized water and freeze-drying to obtain freeze-dried high molecular weight gelatin;
[0012] S112, dissolving the freeze-dried gelatin obtained in step S111 in deionized water, adding dilute hydrochloric acid to adjust the pH to 2.5, adding acetone dropwise with stirring, and then adding glutaraldehyde solution to the gelatin dispersion at room temperature, stirring for 16 hours in a dark place, and then adding glycine aqueous solution to the gelatin dispersion. After stirring for 1 hour, filtering and centrifuging to wash, to obtain amphoteric gelatin nanoparticles.
[0013] In step S1, the method for preparing iron oxide nanoparticles comprises the following steps:
[0014] S121, add 1.08 g of ferric chloride hexahydrate to a mixed solution of 10 mL of ethylene glycol and 30 mL of diethylene glycol, and stir for 30 min;
[0015] S122, adding 0.1 g of polyacrylic acid to the mixed solution of step S121, and stirring for 30 min;
[0016] S123, add 6 g of anhydrous sodium acetate to the mixed solution of step S122, and stir for 1 h;
[0017] S124, placing the mixed solution of step S123 in a high-pressure reactor and reacting it at high temperature, and washing the obtained black product by centrifugation to obtain iron oxide nanoparticles.
[0018] In step S124, the reaction temperature is 200° C. and the reaction time is 12 h.
[0019] In step S1, the method for preparing calcium carbonate nanoparticles comprises the following steps:
[0020] S131, dissolve 150 mg of calcium chloride dihydrate in 100 mL of ethanol;
[0021] S132, take 5 g of ammonium bicarbonate powder and place it in a sealed container;
[0022] S133, placing the mixed solution in step S131 in the sealed container of step S132, and then placing it in an oven to react under vacuum, and centrifugally washing to obtain a white product, which is calcium carbonate nanoparticles.
[0023] In step 133, the reaction temperature is 40° C. and the reaction time is 24 h.
[0024] In the step S1, gelatin nanoparticles, iron oxide nanoparticles, calcium carbonate nanoparticles, and sodium alginate are vortex mixed at pH≈11.
[0025] In the step S2, the solid content of the obtained high mechanical property particle hydrogel is 11.0 w / v% to 13.5 w / v%.
[0026] The invention also discloses the use of the high mechanical property granular hydrogel prepared by the preparation method in the preparation of an interventional embolic agent for combined magnetic heat treatment of liver cancer.
[0027] The present invention introduces sodium alginate and calcium carbonate nanoparticles into the particle hydrogel system of gelatin nanoparticles and iron oxide nanoparticles, realizes the gradual enhancement of mechanical properties in the environment of slow hydrolysis of glucono-δ-lactone, and develops a particle hydrogel with high mechanical properties, abbreviated as Ca-Alg / MCG. Sodium alginate is a natural polyanionic polysaccharide molecule with a strong affinity for divalent ions (such as calcium ions). Divalent ions can combine with α-L-guluronic acid of alginate molecules to form ionic crosslinks, and calcium carbonate gradually dissociates calcium ions and chelates with sodium alginate, slowly enhancing the mechanical properties of the particle hydrogel. The storage modulus of the particle hydrogel can be increased to 11 times the original modulus after two hours. It shows excellent vascular embolization effect in rabbit renal embolism model and liver cancer rabbit embolism model. At the same time, combined with magnetic nanoparticles to respond to alternating magnetic fields to generate heat, further killing tumor cells.
[0028] Compared with the prior art, the beneficial effects of the present invention are:
[0029] 1. The hydrogel prepared by the present invention is a three-dimensional hydrogel network formed by controllable electrostatic assembly of building blocks, and then the natural polysaccharide sodium alginate is chelated with calcium ions to enhance the mechanical properties of the particle hydrogel. It does not involve complex chemical cross-linking and toxic cross-linking agents. Both the synthetic raw materials and the cross-linking method have good biocompatibility, which is conducive to clinical transformation.
[0030] 2. The particle hydrogel with enhanced mechanical properties prepared by the present invention has the dual characteristics of being injectable and having enhanced mechanical properties. Particle hydrogels usually have weak mechanical properties, which limits their application in arterial blood vessels. A common method for improving the mechanical properties of hydrogels is to use irreversible covalent bonds to increase their degree of cross-linking, but this will cause the hydrogel to reduce its injectability. Therefore, the particle hydrogel with enhanced mechanical properties prepared by the present invention has good injectability in the initial stage of preparation, and the mechanical properties can be further improved over time;
[0031] 3. The high mechanical property granular hydrogel prepared by the present invention has good magnetic field responsiveness and can rapidly heat up under an alternating magnetic field to further kill tumors, thereby achieving embolization combined with magnetic thermal synergistic treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The scanning electron microscope image (A) and hydrated particle size diagram (B) of gelatin nanoparticles;
[0033] Figure 2 The scanning electron microscope image (A) and hydrated particle size diagram (B) of iron oxide nanoparticles;
[0034] Figure 3 The scanning electron microscope photo of calcium carbonate nanoparticles (A) and the hydrated particle size diagram (B);
[0035] Figure 4 The scanning electron microscope images of the internal structure of MCG (A) and the scanning electron microscope images of the internal structure of Ca-Alg / MCG (B);
[0036] Figure 5 Photos of MCG and Ca-Alg / MCG casting and demoulding;
[0037] Figure 6 Deformation of MCG and Ca-Alg / MCG under external load;
[0038] Figure 7 Ca 0 -Alg 1 / MCG, Ca 0 -Alg / MCG, Ca 0 -Alg 2 / MCG has an injection force of 2.6F;
[0039] Figure 8 Ca 0 -Alg 1 / MCG, Ca 0 -Alg / MCG, Ca 0 -Alg 2 / MCG embolization pressure;
[0040] Fig. 9 MCG, Ca 0 -Alg / MCG, Ca 0.5 -Alg / MCG, Ca 1.0 -Alg / MCG, Ca 1.5 -Comparison of storage modulus of Alg / MCG before and after gelation;
[0041] Fig.10 For instant preparation of Ca 0 -Alg / MCG, Ca 0.5 -Alg / MCG, Ca 1.0 -Alg / MCG, Ca 1.5 - Shear thinning test of Alg / MCG;
[0042] Fig.11 For instant preparation of Ca 0 -Alg / MCG, Ca 0.5 -Alg / MCG, Ca 1.0 -Alg / MCG, Ca 1.5 -Catheter injection force of Alg / MCG;
[0043] Fig.12 For instant preparation of Ca 1.0 -Peak hold test of Alg / MCG;
[0044] Fig.13 MCG, Ca 1.0 -Modulus variation of Alg / MCG over time;
[0045] Fig.14 is the relationship between the cumulative release of calcium ions and time;
[0046] Fig.15 MCG, Ca 1.0 - embolic pressure of Alg / MCG;
[0047] Fig.16 Ca 1.0 -Digital subtraction angiography (DSA) and X-ray images of Alg / MCG in rabbit renal embolization;
[0048] Fig.17 Computed tomography images (CT images) of the blank control group and 28 days after embolization;
[0049] Fig.18 Color Doppler ultrasound images (CDU images) and contrast-enhanced ultrasound (CEUS images) of the blank control group and 28 days after embolization;
[0050] Fig.19These are the three-dimensional modeling images of the kidneys in the blank control group and 28 days after embolization;
[0051] Fig. 20 The pictures are of the blank control group and the kidneys after embolization for 28 days;
[0052] Fig.21 The images are hematoxylin-eosin staining images of renal tissues on day 0 and day 28 of embolization (H&E staining images);
[0053] Fig. 22 Prussian blue staining images of renal tissue on day 0 and day 28 of embolization (PB staining images);
[0054] Fig.23 Ca 1.0 -Magnetic thermal heating effect of Alg / MCG in tumor model;
[0055] Fig.24 These are X-ray images and DSA images of rabbits with liver cancer before and after tumor vascular embolization;
[0056] Fig.25 These are photos of rabbits with liver cancer without treatment, treated with arterial embolization, and treated with arterial embolization combined with magnetic hyperthermia 14 days later;
[0057] Fig.26 H&E staining images of liver cancer rabbits without treatment, treated by arterial embolization, and treated by arterial embolization combined with magnetic hyperthermia 14 days later;
[0058] Fig. 27 These are PB staining images of rabbits with liver cancer 14 days after no treatment, arterial embolization, and arterial embolization combined with magnetic hyperthermia. DETAILED DESCRIPTION
[0059] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0060] Example 1
[0061] 1. Prepare gelatin nanoparticles, the steps are as follows:
[0062] Spherical gelatin nanoparticles were prepared by a two-step desolvation method.
[0063] (1) 25 g of gelatin was dissolved in 500 mL of 50° C. deionized water. Then, 500 mL of acetone was added to the gelatin solution, and the mixture was allowed to stand at room temperature for 1 hour. The supernatant was removed, and the gelatin precipitate was dissolved again in 50° C. deionized water, and then freeze-dried to obtain high molecular weight gelatin;
[0064] (2) Dissolve 3.75 g of high molecular weight gelatin in 75 mL of deionized water, and then add dilute hydrochloric acid to adjust the pH value of the solution to 2.5. Under stirring at 1000 rpm, add 225 mL of acetone dropwise to the 40°C gelatin solution at a rate of 10 mL / min using a syringe pump. After the reaction solution is cooled to room temperature, add 550 μL of glutaraldehyde solution (25 wt%) and stir at 600 rpm for 16 hours in a dark environment;
[0065] (3) 100 mL of 300 mM glycine aqueous solution was added to the gelatin dispersion prepared in step (2) to remove unreacted aldehyde groups. After stirring for 1 hour, the dispersion was filtered through a sieve with a mesh size of 100 μm. Subsequently, the precipitate was dispersed again in an acetone aqueous solution (volume ratio of acetone: water = 1:3) by centrifugal washing and set aside.
[0066] 2. Prepare ferroferric oxide nanoparticles in the following steps:
[0067] Fe3O4 nanoparticles were prepared by solvothermal method.
[0068] (1) Dissolve 1.08 g of ferric chloride hexahydrate in a mixed solution of 10 mL of ethylene glycol and 30 mL of diethylene glycol, and stir for 30 minutes to completely dissolve it. Then add 0.1 g of polyacrylic acid and stir for 30 minutes. Finally, add 6 g of anhydrous sodium acetate and stir for 1 hour.
[0069] (2) The mixed solution obtained in step (1) was transferred to a high-pressure reactor and reacted at 200° C. for 12 h.
[0070] (3) After the reaction is completed, centrifuge and continuously wash the black product for later use.
[0071] 3. Prepare calcium carbonate nanoparticles, the steps are as follows:
[0072] Calcium carbonate nanoparticles were prepared by vapor diffusion method.
[0073] (1) Dissolve 150 mg of calcium chloride dihydrate in 100 mL of ethanol and place it in a sealed container.
[0074] (2) Place 5 g of ammonium bicarbonate in a sealed container.
[0075] (3) Place the sealed container in an oven at 40°C and react for 24 hours under vacuum. After the reaction is completed, centrifuge and wash the white product for later use.
[0076] 4. Preparation of particle hydrogel with enhanced mechanical properties, the steps are as follows:
[0077] The prepared alkaline (pH ≈ 11) gelatin nanoparticle dispersion, iron oxide nanoparticle dispersion, sodium alginate solution and calcium carbonate nanoparticle dispersion were mixed uniformly by vortexing, and the final concentrations in the system were 8 w / v%, 2 w / v%, 2 w / v% and 1 w / v%, respectively. Then, 50 mg of GDL powder was added to adjust the pH of the system to cause gelation, and the particle hydrogel Ca with enhanced mechanical properties was obtained. 1.0 -Alg / MCG.
[0078] Example 2
[0079] The content of calcium carbonate nanoparticles in this example is 0.5 w / v%, the amount of GDL added is 32 mg, and the other preparation conditions are the same as those in Example 1, which is abbreviated as Ca 0.5 -Alg / MCG.
[0080] Example 3
[0081] The content of calcium carbonate nanoparticles in this example is 1.5 w / v%, the amount of GDL added is 67 mg, and the other preparation conditions are the same as those in Example 1, which is abbreviated as Ca 1.5 -Alg / MCG.
[0082] Example 4
[0083] The content of calcium carbonate nanoparticles in this example is 0, the content of sodium alginate is 2 w / v%, the amount of GDL added is 14 mg, and the other preparation conditions are the same as those in Example 1, which is abbreviated as Ca 0 -Alg / MCG.
[0084] Example 5
[0085] The content of calcium carbonate nanoparticles in this example is 0, the content of sodium alginate is 1 w / v%, the amount of GDL added is 14 mg, and the other preparation conditions are the same as those in Example 1, which is abbreviated as Ca 0 -Alg 1 / MCG.
[0086] Example 6
[0087] The content of calcium carbonate nanoparticles in this example is 0, the content of sodium alginate is 3 w / v%, the amount of GDL added is 14 mg, and the other preparation conditions are the same as those in Example 1, which is abbreviated as Ca 0 -Alg 2 / MCG.
[0088] Comparative Example 1
[0089] The prepared alkaline (pH≈11) gelatin nanoparticle dispersion and iron oxide nanoparticle dispersion were mixed uniformly by vortexing, and the final concentrations in the system were 8w / v% and 2w / v%, respectively. Then, 14 mg of GDL powder was added to adjust the pH of the system to cause gelation, and a high mechanical property particle hydrogel was obtained, which was abbreviated as MCG.
[0090] Figure 1 The scanning electron microscope photo and hydrated particle size diagram of gelatin nanoparticles. The gelatin nanoparticles have a uniform and smooth surface and a particle size of about 240nm. Figure 2 The following is a scanning electron microscope photo of iron oxide nanoparticles and a hydrated particle size diagram. The iron oxide appears as rough round particles with a particle size of about 130nm. Figure 3 This is a scanning electron microscope photo of calcium carbonate nanoparticles and a hydrated particle size diagram. The particle size is about 110nm.
[0091] Figure 4 The internal structures of the gelled particle hydrogel (MCG) and the high mechanical properties particle hydrogel (Ca-Alg / MCG) were compared. The results showed that MCG was only a three-dimensional network formed by particle assembly, while Ca-Alg / MCG showed a polymer network wrapped around the nanoparticles. Figure 5 The shapes of particle hydrogel (MCG) and high mechanical performance particle hydrogel (Ca-Alg / MCG) after casting and demolding were compared. Compared with MCG, Ca-Alg / MCG has finer contours after demolding and can be picked up by tweezers, showing better mechanical properties. Figure 6 It shows that Ca-Alg / MCG can resist external force and is not easy to deform. It can return to its original shape after the external force is removed, and has stronger mechanical properties than MCG.
[0092] In order to clarify the effect of sodium alginate content on the mechanical properties of particle hydrogel, different contents of sodium alginate were added to the particle hydrogel MCG. Figure 7 It can be seen that when the content of sodium alginate is 3w / v%, the force required for the particle hydrogel to pass through a 2.6F catheter at an injection rate of 1mL / min exceeds 50N, and it cannot be injected. When the content of sodium alginate is 1w / v% and 2w / v%, the injection force is less than 50N, and it is easy to inject through the catheter. Figure 8 The embolism pressure of these three hydrogels with different sodium alginate contents was tested. When the sodium alginate content was 1w / v%, its embolism pressure was lower than the physiological arterial pressure of humans (16kPa), while the embolism pressures of the other two hydrogels exceeded 16kPa, indicating that they have a certain ability to resist blood shock.
[0093] Fig. 9The storage modulus of the hydrogels in Example 1, Example 2, Example 3, Example 4, and Comparative Example 1 before and after gelation were compared. In Comparative Example 1, MCG was gelated by electrostatic assembly, so that its storage modulus increased from 192.2±11.0Pa to 312.4±27.2Pa. 0 -Alg / MCG storage modulus after gelation is 573.3±15.6Pa, which has no significant effect on the storage modulus of MCG. 1.0 -Alg / MCG increased from 615.7±39.8Pa to 7284.5±164.2Pa before and after gelation, showing excellent mechanical properties. 0.5 The storage modulus of -Alg / MCG after gelation is relatively low, 3306.4±56.9Pa, because the content of calcium carbonate nanoparticles is low, which ultimately leads to too low a degree of crosslinking. 1.5 -Alg / MCG storage modulus after gelation is 5376.7±119.7Pa. In this example, the content of calcium carbonate nanoparticles is too high, and excessive calcium ions are unevenly chelated with sodium alginate, which hinders the formation of symmetrical "egg box" dimers and leads to cross-linking between and within alginate molecules, ultimately reducing the hardness of the gel. It can be seen that the mechanical properties of the gel in Example 1 are most significantly improved.
[0094] Fig.10 The shear thinning properties of the instant prepared hydrogels of Example 1, Example 2, Example 3, and Example 4 were tested, and the viscosity thereof decreased with increasing shear rate. Fig.11 The catheter injectability of the hydrogels prepared in Example 1, Example 2, Example 3, and Example 4 was tested, and the injection forces through the 4F catheter were 12.4±0.3N, 12.2±0.1N, 14.8±0.3N, and 10.6±1.1N, respectively, and the injection forces through the 2.6F catheter were 27.8±0.7N, 26.8±0.8N, 31.2±0.9N, and 25.8±0.9N, respectively. The results show that the hydrogels prepared in Example 1, 2, 3, and 4 all have good catheter injectability.
[0095] To evaluate the viscosity change of the hydrogel during extrusion through the catheter, a peak hold test was performed. Fig.12 As shown, at the beginning of the extrusion process, the hydrogel was subjected to a low shear rate (0.01s -1 ). Subsequently, as the hydrogel passed through the catheter, the shear rate was increased to 1140 s -1 , and then dropped sharply after the hydrogel left the catheter tip (0.01s -1 ). The results show that the Ca prepared in Example 1 1.0-Alg / MCG not only exhibits shear-thinning behavior but also recovers to the original viscosity under the above shear rate changes. Fig.13 The Ca prepared in Example 1 was tested 1.0 -Alg / MCG modulus changes with time. It can be seen that its storage modulus starts to increase at about 4 minutes and reaches a plateau at about 80 minutes, indicating that the modulus change in Example 1 increases with time and can provide sufficient surgical time for clinicians. Fig.14 As shown, the relationship between the cumulative release of calcium ions and time was tested. It can be seen that the release amount gradually increased with time, and the release amount was about 90% at around 80 minutes, which indirectly confirmed the time-varying characteristics of the modulus of the hydrogel in Example 1. Fig.15 The maximum pressure that the hydrogels in Comparative Example 1 and Example 1 can withstand is shown. The embolization pressure of MCG is about 12.1±1.6 kPa, while that of Ca 1.0 The embolization pressure of -Alg / MCG increased from the initial 22.2±1.2 kPa to 69.9±6.0 kPa, which confirmed that the mechanical properties of Example 1 were improved with the increase of time.
[0096] The rabbit renal embolism model was used to evaluate the embolism effect of Example 1. Fig.16 As shown in the figure, before embolization, the DSA image shows obvious outlines of both kidneys and the direction of blood vessels. The hydrogel of Example 1 was immediately prepared and mixed with iodixanol, and injected into the right renal artery through a catheter. The X-ray image data showed that the hydrogel was enriched in the renal artery and small blood vessels. The DSA image after embolization showed a clear outline of the left kidney, while the right renal blood vessels were not developed, indicating that the right kidney was completely embolized. Fig.17 As shown, CT imaging data 28 days after embolization showed that the volume of the right kidney was significantly reduced. Fig.18 The CDU and CEUS images were taken 28 days after embolization. The results showed that the kidney was reduced in size and had no blood supply 28 days after embolization. Fig.19 The three-dimensional modeling imaging data showed that the right renal artery and kidney were not visible 28 days after embolization. Fig. 20 Figure 2 is a photo of a kidney 28 days after embolization, which also shows that the right kidney is atrophied, indicating that the hydrogel in Example 1 has a good embolization effect. Fig.21 As shown, H&E staining images of renal tissues showed that on the 28th day after embolization, the nuclei of renal tissue cells showed large-scale deformation and apoptosis, and large-scale tissue necrosis. Fig. 22 PB staining of renal tissue confirmed the long-term retention of the hydrogel in the renal blood vessels and its ability to stably and effectively embolize the blood vessels.
[0097] Iron oxide nanoparticles have excellent magnetic response properties. A tumor model was used to evaluate whether the magnetothermal effect of high mechanical performance particle hydrogels under an alternating magnetic field can kill tumor edge cells. An infrared camera was used to monitor the surface temperature of the tumor model, and an optical fiber temperature sensor was used to measure the temperature changes inside the tumor model. Fig.23 At a field strength of 25 kA / m, the surface temperature of the tumor model can reach 45°C after about 20 minutes, confirming that the hydrogel can kill tumor edge cells under an alternating magnetic field. Liver cancer rabbits were used to verify the embolization and magnetic thermal treatment effects of the hydrogel in Example 1. Fig.24 As shown, the tumor location (green circle) and the tumor supplying artery can be seen before embolization. After embolization, the tumor location is not visualized, confirming that the tumor blood vessels have been embolized. Fig.25 The following are photos of the livers of the untreated group, the transarterial embolization group, and the transarterial embolization combined with magnetic thermal therapy group 14 days later. The results show that the tumor volume in the untreated group was significantly larger. After transarterial embolization, the tumor volume decreased, proving that embolization can inhibit tumor progression. After transarterial embolization combined with magnetic thermal therapy, the tumor volume was the smallest, indicating that magnetic thermal therapy can further inhibit tumor growth on the basis of embolization therapy. Fig.26 The H&E staining images of tumor tissues showed that compared with the transarterial embolization treatment group, the transarterial embolization combined with magnetic thermal therapy group had more tumor cell nuclear deformation and apoptosis, as well as large-area tissue necrosis, indicating that magnetic thermal therapy can significantly improve the effect of embolization therapy. Fig. 27 The above experimental results show that the hydrogel in Example 1 exhibits a stable and long-term embolization effect in the embolization of tumor blood vessels in rabbits with liver cancer, and can be combined with magnetic thermal therapy to improve the efficacy.
[0098] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A method for preparing a granular hydrogel with high mechanical properties, characterized in that: The following steps are involved: S1, mixing gelatin nanoparticles, iron oxide nanoparticles, calcium carbonate nanoparticles, and sodium alginate under alkaline conditions; S2, adding glucono-δ-lactone powder to adjust the pH to obtain a particle hydrogel with high mechanical properties.
2. The method for preparing a particle hydrogel with high mechanical properties according to claim 1, characterized in that: In step S1, the method for preparing gelatin nanoparticles comprises the following steps: S111, heating gelatin to dissolve in deionized water to obtain a gelatin solution, adding acetone, standing at room temperature for 1 hour, removing the supernatant, dissolving the precipitate again in deionized water and freeze-drying to obtain freeze-dried high molecular weight gelatin; S112, dissolving the freeze-dried gelatin obtained in step S111 in deionized water, adding dilute hydrochloric acid to adjust the pH to 2.5, adding acetone dropwise with stirring, and then adding glutaraldehyde solution to the gelatin dispersion at room temperature, stirring for 16 hours in a dark place, and then adding glycine aqueous solution to the gelatin dispersion. After stirring for 1 hour, filtering and centrifuging to wash, to obtain amphoteric gelatin nanoparticles.
3. The method for preparing a particle hydrogel with high mechanical properties as claimed in claim 1, characterized in that: In step S1, the method for preparing iron oxide nanoparticles comprises the following steps: S121, add 1.08 g of ferric chloride hexahydrate to a mixed solution of 10 mL of ethylene glycol and 30 mL of diethylene glycol, and stir for 30 min; S122, adding 0.1 g of polyacrylic acid to the mixed solution of step S121, and stirring for 30 min; S123, add 6 g of anhydrous sodium acetate to the mixed solution of step S122, and stir for 1 h; S124, placing the mixed solution of step S123 in a high-pressure reactor and reacting it at high temperature, and washing the obtained black product by centrifugation to obtain iron oxide nanoparticles.
4. The method for preparing a particle hydrogel with high mechanical properties as claimed in claim 3, characterized in that: In step S124, the reaction temperature is 200° C. and the reaction time is 12 h.
5. The method for preparing a particle hydrogel with high mechanical properties as claimed in claim 1, characterized in that: In step S1, the method for preparing calcium carbonate nanoparticles comprises the following steps: S131, dissolve 150 mg of calcium chloride dihydrate in 100 mL of ethanol; S132, take 5 g of ammonium bicarbonate powder and place it in a sealed container; S133, placing the mixed solution in step S131 in the sealed container of step S132, and then placing it in an oven to react under vacuum, and centrifugally washing to obtain a white product, which is calcium carbonate nanoparticles.
6. The method for preparing a particle hydrogel with high mechanical properties as claimed in claim 5, characterized in that: In the step S133, the reaction temperature is 40° C. and the reaction time is 24 h.
7. The method for preparing a particle hydrogel with high mechanical properties as claimed in claim 1, characterized in that: In the step S1, gelatin nanoparticles, iron oxide nanoparticles, calcium carbonate nanoparticles, and sodium alginate are vortex mixed at pH≈11.
8. The method for preparing a particle hydrogel with high mechanical properties as claimed in claim 1, characterized in that: In the step S2, the solid content of the obtained high mechanical property particle hydrogel is 11.0 w / v% to 13.5 w / v%.
9. A particle hydrogel with high mechanical properties prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the high mechanical property particle hydrogel as claimed in claim 9 in the preparation of an interventional embolic agent for combined magnetic thermal treatment of liver cancer.
Citation Information
Patent Citations
Hydrogel and preparation method thereof
CN112089886A
Preparation method of multi-network natural polymer physical hydrogel
CN114989454A
Preparation method of dual-network hydrogel loaded with functional components
CN115073768A
Embolization hydrogel having controllable degradation time, and preparation method therefor
US20240197952A1
Cited By
Injectable temperature response enhanced composite dual-network magnetic particle gel as well as preparation method and application thereof
CN120437363A
Injectable temperature-responsive enhanced double network magnetic particle hydrogel, preparation method and application thereof
CN120437363B